Chemical Synthesis and Characterization of Conducting Polyaniline - Hasoon et al. (مجلة بغداد للعلوم, 2020)
The polyaniline powder was chemically manufactured by direct oxidation of aniline. The resulting polymer was characterized by the results of optical, measurements by (FT-IR) spectroscopy, we have detected some of the absorption peaks located at 3498, 2858 cm-1, which correspond N-H vibrations, and C-H expansion of the aromatic ring respectively as well as stretching vibrations of quinoid ring have been observed. Structural properties, such as the surface topography using an atomic force microscope (AFM), and Surface composition by (SEM) have been studied. The structure of some pellets of polyaniline powder have been examined by using analytical X-ray diffraction technique, the pattern of observed lines shows a crystalline nature and three large peaks observed.